2021
DOI: 10.1080/1354750x.2021.1875506
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine biomarkers as indicators of human disease

Abstract: The significant increase of periodontitis, chronic kidney disease (CKD), Alzheimer's disease and cancer can be attributed to an ageing population. Each disease produces a range of biomarkers that can be indicative of disease onset and progression. Biomarkers are defined as cellular (intra/extracellular components and whole cells), biochemical (metabolites, ions and toxins) or molecular (nucleic acids, proteins and lipids) alterations which are measurable in biological media such as human tissues, cells or flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 206 publications
(209 reference statements)
0
19
0
Order By: Relevance
“…Spermine was also utilized to detect and discriminate pancreatic cancer from other malignancies. Salivary spermine level in pancreatic cancer patients was a potential indicator of pancreatic cancer as spermine exhibited a specific and increased level in cancerous patients [39]. On the other hand, unlike traditional blood-taking-based cancer screening tests, being a non-invasive liquid biopsy, urine and saliva can be readily and easily obtained from patients without causing any discomfort.…”
Section: Detection and Prognosismentioning
confidence: 99%
“…Spermine was also utilized to detect and discriminate pancreatic cancer from other malignancies. Salivary spermine level in pancreatic cancer patients was a potential indicator of pancreatic cancer as spermine exhibited a specific and increased level in cancerous patients [39]. On the other hand, unlike traditional blood-taking-based cancer screening tests, being a non-invasive liquid biopsy, urine and saliva can be readily and easily obtained from patients without causing any discomfort.…”
Section: Detection and Prognosismentioning
confidence: 99%
“…Polycationic polyamines Spd and Spm are essential for mammalian cell growth and survival. Dysfunction of them has been implicated in human health and diseases, such as cancer, inflammation, stroke, renal failure, diabetes, cardiovascular disease, cognitive impairment, and other ailments ( Amin et al, 2021 ). Mostly, Spd shares similar biological activities to Spm, but sometimes they showed a diverse mechanism in various pathological and physiological conditions or in the different cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown cadaverine enhances the effectiveness of many β-lactams against P. aeruginosa ( Kwon and Lu, 2006 ; Manuel et al., 2010 ). Cadaverine is a natural metabolite found in all living organisms ( Miller-Fleming et al., 2015 ) and can stem from microbiota or have endogenous origin ( Amin et al., 2021 ). Cadaverine supplementation shows low acute oral toxicity at 2,000 mg/kg body weight in rats ( Til et al., 1997 ), and negligible cytotoxicity up to 70 mM in HT29 intestinal cells ( del Rio et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%